Microsoft Visual BASIC .NET language reference. - Safari eBooks (Redmond, Wash. : Microsoft Press, 2002)
"Here's official documentation for the Visual Basic .NET language, including descriptions of language and run-time elements including attributes, data types, functions, methods, objects, operators, properties, statements, and more"--Resource description page.
Description based on print version record.
Keywords: Microsoft Visual BASIC; BASIC (Computer program language); Electronic books